ENTERPRISE RISK MANAGEMENT DAN KINERJA PERUSAHAAN BUMN: TINJAUAN LITERATUR SISTEMATIS DAN IMPLIKASINYA BAGI PT PLN (PERSERO) - Mujiono Yunus; Arifuddin Mannan (PT. Hasba Edukasi Mandiri, 2026)
State-owned enterprises manage large assets and vital public services. PT PLN (Persero) faces interrelated operational, financial, and regulatory risks. Enterprise Risk Management (ERM) offers an integrated approach to manage these risks. This article reviews the literature on the relationship between ERM adoption and firm performance, focusing on the context of state-owned enterprises. The author applies a Systematic Literature Review method. Articles were selected from Google Scholar, Garuda, and DOAJ for the 2015 to 2026 period. The review shows that ERM adoption relates positively to firm performance and firm value in most studies. Some studies report insignificant effects on specific indicators. The COSO framework remains the dominant reference for measuring ERM. This article develops practical implications for PT PLN (Persero) to strengthen its risk governance. The author also identifies a research gap regarding state-owned enterprises in the energy sector.